The Effectiveness of Criminal Law Jurisdiction on Children in Indonesia - Adi Mansar (RIRAI Publisher, 2022)
The range of instances of violence in opposition to kids has left many query marks on how some distance the position of the kid safety regulation itself is. Law Number eleven of 2012 regarding the Juvenile Justice System withinside the Preamble letter reads